The Impact of a Balanced Vegetarian Diet on Healthy Pregnancy Development: A Literature Review - Racisz, Kinga; Duda, Joanna; Kędzia, Jakub; Obcowska, Alicja; Walendzik, Aleksandra; Sencerek, Łukasz; Racisz, Paweł (Quality in Sport, 2025)
Introduction According to data, 5% of people in Europe and 6% of people in Poland are vegetarians. Therefore, an increasing percentage of pregnant women will follow a plant-based diet. During pregnancy, the need for vitamins and minerals increases, and the proper balance and possible supplementation of a vegetarian diet are crucial for proper fetal development and a pregnant woman's health. Aim of study This study aims to evaluate and compare information regarding the adequacy of a vegetarian diet for pregnant women and its impact on maternal outcomes, fetal development, newborn health and lactation. Materials and methods The search methodology incorporated the terms “vegetarian diet” or “plant-based diet” or “vegan” AND “pregnancy” or “pregnant” or “health benefits”, along with variations of these terms, found in many scientific databases. Publications issued before 2019 and case reports were excluded. Conclusion There is a consensus that a plant-based diet is safe during both pregnancy and lactation. Nevertheless, it may be associated with many nutrient deficiencies. A vegetarian diet promotes a lower incidence of excessive weight gain, which results in a less frequent occurrence of EWG-related complications. There was no higher prevalence of premature births or infant mortality. The occurrence of gestational diabetes, small gestational age/low birth weight and congenital anomalies require further study. Breastfeeding during a vegetarian diet is possible, but appropriate supplementation is recommended.